FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PADI DI SUMATERA BARAT - Anugrah Ramadhana Putra; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This research aims to analyze what factors influence rice production in West Sumatra. This research uses primary data in the form of a questionnaire given directly to rice farmers in Pancung Soal District. This research uses 2 (two) variables, namely the dependent variable in the form of production and income, then the independent variables are fertilizer, medicine, production costs, labor, harvest prices, and farmer's age. The type of research used is quantitative descriptive research, namely describing the influence between variables then expressed in numbers and explained by comparing existing theories and using data analysis techniques that are appropriate to the variables in this research. The results of this research show that (1) fertilizer is able to increase rice production in West Sumatra. (2) medicines have a big influence on rice production in West Sumatra. (3) Labor has a large and negative influence on rice production in West Sumatra. (4) Production costs have a big influence on rice income in West Sumatra. (5) harvest prices have a significant effect on rice income in West Sumatra. (6) Farmer age has a big influence on rice income in West Sumatra. (7) The amount of production is in line with rice income in West Sumatra Keywords: Income, Production, and Rice